ANALISIS PRODUK DAN PROSES MANUFAKTURING GUNA MENINGKATKAN EFISIENSI DAN EFEKTIFITAS (Dinamika Ekonomi, 2003)
The analysis of product and manufacturing process is the innitiate activity andbecome a base in ptunning an industrial activity' Tht tttot in the early analysis willcause afataleffect in the following process'product .rriyil i, un aciivity which will change the last product into thecomponents of the product former in detail : specification, volume, and the amount ofthe product. tvtean*trii. pro..r, analysis is plan of a step which is needed to makeunoth., product from the early to the end of the process'